RETURNS AND MARKET POSITIONS OF COMMERCIAL BANKS IN PRODUCT POSITIONING OF FINANCIAL PRODUCTS FOR THE NEEDS OF AGRICULTURE IN BULGARIA - Tzvetelina Borisova (Journal of Bio-Based Marketing)
In recent years, Bulgarian agriculture has emerged as one of the fastest-growing sectors of the national economy. The main reason for this expansion lies in the following factors – (1) the huge financial resources available to agricultural holdings in the form of subsidies and investment support grants; (2) the strategic importance of the sector for rural development; and (3) the large number of people employed in this economic activity in areas where there is no other economic alternative for employment. Undoubtedly, this rapid development of agriculture cannot be achieved without the effective intervention of the banking sector. The significant investments made in agricultural holdings have been made through their own co-financing added to the financial assistance received from the European Structural Funds. This co-financing is very often provided through lending by commercial banks (M’kuma, 2015); (Saravani & Mahmodpour, 2015). All these arguments determine the relevance of the present study on the effects of financial product positioning strategies on the needs of agriculture. The purpose of the article is to evaluate the profitability and market performance of commercial banks as a result of applied product positioning strategy for the needs of farmers in Bulgaria.